Water Resources, Human Rights and Governance - Iyer, Ramaswamy R. (Water Nepal, 2004)
This paper traces certain developments in broad terms without straying too far from the theme of water. The reference will be to the Indian experience, but I hope that what I say will have a relevance beyond that context. The process of economic development that India embarked on as an independent nation can be encapsulated as the objective was to be ‘development’, by which was meant what was to be seen in the Western world, the agent for bringing this about was to be the state, the route was to be centralised economic planning (under the influence of Fabian socialism and the Soviet planning model), and the tool was to be Science and Technology (again, as exemplified in the West, reflecting the Promethean legacy). Alongside of ‘development’, a parallel goal that India’s leaders wished to pursue was ‘modernity’. There was an implicit assumption among the intelligentsia that India needed to move away from its traditional ways to the modern world – which again was what could be seen in the West. Nehru, like Kamal Ataturk, was a moderniser and westerniser, though there was also in him the contrary influence of Gandhi. Another strand of some importance in the early years after Independence was that for a number of historical reasons there was a desire to maintain a strong and stable central government. That was why India went in for a form of quasi-federalism and not federalism in the fullest sense. The word ‘federal’ did not figure in the Indian Constitution, and the Constitution had several unitary features. Water Nepal Vol.11, No.1, 2004, pp.